The Concept of Islamic Education Based on Religious Humanism Said Nursi's Perspective - Afif Alfiyanto; Syamsul Rijal; Silahuddin Silahuddin (Journal on Education, 2023)
Said Nursi's first effort was to make people aware of the importance of education, where Islam is "education for the people." An awareness of the unity and cohesiveness of modern religion and science accompanies this effort. This is where Said Nursi's position emerges as a reformer who wants to make improvements to "save faith and Islam." Said Nursi, in the practice of Islamic Education has the character of religious humanism thinking, which is a spiritual concept that places man by the purpose of his creation by the Creator, as well as efforts to teach sciences while still being based on faith, understanding of the Qur'an, the last day and scientific synergy. This concept is an attempt to unite religious values with humanity. Religion is not only a belief system but also a humanitarian-oriented deal. Thus, Islamic education based on religious humanists in the perspective of Bediuzzaman Said Nursi is a concept that can develop human potential, both worldly and ukhrowi aspects, to create a balanced person about fellow beings (hablun minannas) and with the Creator (hablun minallah).